Effect of Working Capital Management on Firms’ Profitability: Empirical Evidence from Malaysia - Cheng, Mui Gek (2013)
Working capital management influence the profitably of the company and ultimately determine the firm value and the firm value is among the most important criteria for any shareholders or potential shareholders to decide whether to invest or not to invest. Inefficiency in managing the working capital will result in insolvency or eventually lead to bankruptcy. In other words, managers should ponder all the elements that will affect the working capital management. Consequently, the objective of this research paper is to examine the effects of working capital management on firms’ profitability in Malaysia and to provide better justification. In order to do so, a sample of 70 public listed companies from Bursa Malaysia was randomly selected and secondary data from the companies audited accounts from the years of 2010 to 2011 are collected and SPSS quantitative analysis was used and focused on multiple regressions. The results indicate that there is significant relationship between working capital management and profitability, therefore efficient working capital policy can improve profitability of the company and ultimately shareholders wealth.